A Fatal Case of Benzyl Benzoate Poisoning - Teera Kolladarungkri (Siriraj Medical Journal, 2020)
We present a case of benzyl benzoate ingestion in a 38 years old Thai woman whose presenting symptom was coma and severe metabolic acidosis. The amount ingested was 360ml of 25%W/V benzyl benzoate. It did not contain any alcohol or acid substance. Standard textbooks and other reference books do not mention severe symptoms caused by ingestion of given this substance and gastric lavage is the only recommendation. Should there be another method used to induce elimination of benzyl benzoate-hemodialysis?